Socioeconomic status and the prevalence of skin and atopic diseases in five European countries - Ofenloch, Robert; Diepgen, Thomas L. (Acta dermato-venereologica, 2019)
The aim of this study was to investigate the association between socioeconomic status and the prevalence of self-reported skin and atopic diseases in the general population of 5 European countries. A random sample was drawn from the general population aged 18–74 years, based on electoral precincts. Socioeconomic status was estimated by combining net household income with the highest education of respondents. A total of 7,904 subjects were included in this analysis. The lifetime prevalence of “contact dermatitis” ranged from 13.1% (95% confidence interval (95% CI 11.8–14.4%) in subjects with low socioeconomic status, to 19.1% (95% CI 17.5–20.8%) in those with high socioeconomic status. In younger subjects skin cancer was more prevalent in the middle or high socioeconomic status groups compared with the low socioeconomic status group (odds ratio 2.4; 95% CI 1.4–4.3); however, this effect was not found in elderly subjects. The lifetime prevalence for at least one atopic disease was 61.2% (95% CI 59.4–63.0%) in the low and 82.8% (95% CI 81.1–84.3%) in the high socioeconomic status group. Individuals with middle or high socioeconomic status reported an overall higher prevalence of skin and atopic diseases compared with those with low socioeconomic status. These findings may reflect differences in reporting, which are likely to result in an underdiagnoses, especially for skin cancer in the younger age groups with low socioeconomic status.